2015
DOI: 10.1039/c5ra21480g
|View full text |Cite
|
Sign up to set email alerts
|

Confinement effects of graphene oxide nanosheets on liquid–solid phase transition of water

Abstract: In this work, the liquid–solid phase transition temperature of water confined between two graphene oxide (GO) sheets is investigated using molecular dynamics simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The surface roughness and chemical morphology are also important factors affecting the antiicing ability of the surface. It has been found that the freezing delay time of surface with nano‐roughness similar to critical nucleation radius is ten times longer compared with that with larger roughness …”
Section: Introductionmentioning
confidence: 99%
“…The surface roughness and chemical morphology are also important factors affecting the antiicing ability of the surface. It has been found that the freezing delay time of surface with nano‐roughness similar to critical nucleation radius is ten times longer compared with that with larger roughness …”
Section: Introductionmentioning
confidence: 99%
“…Graphene oxide (GO) has been considered a convenient substitute for graphene in important technological applications due to its remarkable electrical, mechanical and thermal properties. [1][2][3][4][5][6][7][8][9][10] The advantages of GO in relation to pure graphene are due to the drastic structural and electronic changes resulting from the functionalization of graphene with oxygen groups. [1][2][3][4][5][6][7][8][9][10] It is well known that the detailed atomic structure of GO is very difficult to obtain since this material is non-stoichiometric, presenting a wide variety of compositions which depend inherently on the route of synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Their results indicated that the ordering of interfacial liquid water on a graphene surface was the main reason for the facilitated heterogeneous nucleation [33]. Not only a promoting material, graphene and its derivatives can also restrain ice formation under specific conditions [22,34]. The exceptional Joule's heating effect and electrothermal effect of graphene-based composites have received much attention in the design of antiicing systems [35,36].…”
Section: Introductionmentioning
confidence: 99%